Ten-day bismuth-containing quadruple therapy is effective as first-line therapy for Helicobacter pylori–related chronic gastritis: a prospective randomized study in China. (June 2017) - Wang, L.; Lin, Z.; Chen, S.; Li, J.; Chen, C.; Huang, Z.; Ye, B.; Ding, J.; Li, W.; Wu, L.; Jiang, Y.; Meng, L.; et al.
Abstract: Objectives: To investigate the effectiveness of 10-day bismuth-containing quadruple (B-quadruple) treatment as first-line therapy in patients with Helicobacter pylori –related chronic gastritis. Methods: A randomized controlled trial was conducted from October 2011 to December 2013 in Zhejiang, China, including patients with H. pylori –related chronic gastritis who were randomly provided either 10-day omeprazole-based triple therapy (OM-triple; omeprazole 20 mg twice daily, clarithromycin 500 mg twice daily and amoxicillin 1 g twice daily) or 10-day B-quadruple therapy (OM-triple + bismuth subcitrate 120 mg four times daily). H. pylori status, pathologic findings and dyspeptic symptoms were assessed at baseline and after 3 months. The primary outcome was H. pylori eradication rates by intention-to-treat (ITT) and per-protocol (PP) analyses. The secondary outcomes were the histologic and symptomatic benefits from H. pylori eradication. Results: A total of 351 patients with H. pylori –related chronic gastritis were recruited. The eradication rates of the OM-triple and B-quadruple groups were 58.4% (108/185) and 86.1% (143/166) respectively according to ITT analysis (p <0.01). PP rates of H. pylori eradication were 63.2% (108/171) and 92.3% (143/155) respectively (p <0.01). According to the PP analysis, active and chronic inflammation in gastric mucosa was substantially improved in all treated patients ( n = 326). However, pathologic atrophic gastritis and intestinal metaplasia did not regress in both groups ( n = 326). The reduction of dyspeptic symptoms score was significantly higher in the B-quadruple group than in the OM-triple group (0.59 ± 0.057 vs. 0.39 ± 0.046) (p <0.01). Conclusions: Ten-day B-quadruple therapy is more effective than OM-triple therapy as first-line therapy for patients with H. pylori –induced chronic gastritis in China.